Influence of investors’ behaviour on investment performance: a study on individual investors at colombo stock exchange in northern province of sri lanka. - Pratheepan, N.; Rathiranee, Y. (Faculty of Management Studies and Commerce, University of Jaffna, Sri Lanka, 2019)
The main objective of this study is to investigate the influence of investors’ behaviour on the investment performance of individual investors at CSE in Northern Province. In addition to that to give some suggestions for individual investors at CSE in Northern Province to adjust their behaviors to achieve good investment results. Stock market playsan important role to gain good return for the investors’ money. Further stock market contributes more to economy for the development through extending the investments in the country especially for Sri Lanka as a developing country. As there are limited studies about behavioral finance in Sri Lanka, this study is expected to contribute significantly to the development of this field in Sri Lanka with a view to enhance the development of Northern Province. The study begins with the existing theories in behavioral finance, based on which, hypothesis is proposed. Then, these hypotheses are tested through the questionnaires distributed to individual investors at the Colombo Stock Exchange. The sample respondents were selected under Proportionate stratified random sampling method as district wise and the data were collected from the sample of 100 individual investors at Colombo Stock Exchange in Northern Province. The collected data were analyzed by using SPSS. Statistical techniques which are used for the data to achieve the research objectives include Descriptive Statistics, Correlation Analysis and Regression Analysis.The resultsrevealed that the Heuristic factor have positive significant influence on the investment performance. Whereas other three factors (Prospect, Market and Herding) have no significant influence on the investment performance.
Keywords: Behavioural Finance; Colombo Stock Exchange; Investors’ behaviour; Investment Performance